New records of pyralid moths (Lepidoptera: Pyraloidea) in the Altai Republic, Russia - A.E. Naydenov; A.N. Streltzov (Кавказский энтомологический бюллетень)
First faunistic records of 11 species of phycitine moths (Pyralidae) and one species of grass pyralid moth (Crambidae) in the Altai Republic of Russia are presented. Christophia granulella (Zerny, 1914) and Yelenka calciferella uyghurica Trofimova et Shovkoon, 2020 are recorded for Russia for the first time, and Cadra furcatella (Herrich-Schäfer, 1849) is recorded for the Asian part of Russia for the first time.